The Influence of Trust on Purchase Decisions of Muslim Fashion Products in Pekanbaru City with Ar-Ridho as a Mediating Variable on Generation-Z in Pekanbaru City - Yusnidar, Yusnidar; Indrastuti, Sri; Mardatillah, Annisa (Journal of Applied Business and Technology, 2025)
This study aims to analyze the influence of trust on purchasing decisions for Muslim fashion products in Pekanbaru City with ar-ridho as a mediating variable. This study responds to the increasing trend of consumption of Muslim fashion products among religious urban communities. Using a quantitative approach, indicators for each variable were developed based on previous literature and empirical data. The number of samples collected and eligible for analysis in this study was 112 Respondents. The results showed that trust has a significant influence on purchasing decisions, and ar-ridho strengthens the relationship as a mediating variable. Muslim fashion brands need to prioritize honesty, transparency, and adherence to sharia to build consumer trust. It is recommended to continue to consider the sharia and sincerity aspects in every consumption decision so that it not only fulfills worldly needs but also has worship value.